Functioning And Organization of Pharmacies Activities in Poland in Accordance with The Principle of Sustainable Development – A Perspective of Fiscal Policy and Legal Regulations - Michal JACHOWICZ; Piotr PODSIADLO (Communications of International Proceedings, 2022)
The purpose of the study was to understand the functioning and organization of pharmacies in Poland in terms of the principle of sustainable development, including in particular the fiscal policy as the basic mechanism for implementing the above principle. Considering that an objective and comprehensive assessment of the impact of the discussed changes in legal regulations on the actual state and direction of development of the pharmacy market and the provision of pharmaceutical services requires a specific time perspective, the possible presentation of the subject of the analysis in the context of the implementation of the sustainable development goals allows for expressing a belief that further regulatory changes, including in particular: 1) strengthening the competitiveness of pharmacies operated by pharmacists compared to pharmacies operated by other entities; 2) ensuring superiority, independence and autonomy in the field of managerial and professional activities carried out by pharmacists as part of the activities of pharmacies. The affirmation of the proposed solutions is an indispensable condition for increasing the quality of public health protection and healthcare services perceived both as the overriding goal of pharmacies and as an important and integral element of the implementation of the principle of sustainable development.
Keywords: Pharmaceutical law; pharmacy market; community pharmacy; sustainable development; fiscal policy; Poland